A Content Analysis of Arabic and English Newspapers before, during, and after the Human Papillomavirus Vaccination Campaign in the United Arab Emirates - Elbarazi, Iffat; Raheel, Hina; Cummings, Kim; Loney, Tom (Frontiers in Public Health, 2016)
Background Cervical cancer is the fourth most common cancer among females in the United Arab Emirates (UAE) with an estimated incidence of 7.4 per 100,000 persons per year. In March 2008, the Health Authority of Abu Dhabi launched a free school-based campaign to provide all female Emirati students aged 15–17 years in the emirate of Abu Dhabi with the human papillomavirus vaccine (HPVV). Despite the proven efficacy of the HPVV in clinical trials, there has been limited research exploring the acceptance of this vaccine within a conservative Islamic society. The media plays a key role in changing beliefs and attitudes toward specific public health initiatives, such as vaccination programs. The primary aim of this study was to explore the content and communication style of the UAE newspapers (both Arabic and English) before, during, and after the HPV vaccination program. Methods A systematic literature search was conducted on six national newspapers with the highest circulation figures in the UAE (Arabic: Al Ittihad, Al Khaleej, and Emarat El Youm; English: Khaleej Times, The National, and Gulf News) to retrieve articles related to cervical cancer prevention from January 2000 to May 2013. One bilingual researcher (Arabic–English) utilized content analysis to study the subject matter of communication in each article. Results A total of 79 newspaper articles (N = 31 Arabic) were included in the study. Content analysis coding revealed five main themes: (i) “HPV Screening or Vaccination Programmes in the UAE” (N = 30); (ii) “Cervical Cancer Statistics in the UAE” (N = 22); (iii) “Aetiology of Cervical Cancer and HPVV Efficacy” (N = 12); (iv) “Cultural Sensitivity and Misconceptions Surrounding HPVV in School-Aged Females” (e.g., promoting promiscuity) (N = 8); and (v) “Cost-Effectiveness, Efficacy, and Safety” (N = 7). Conclusion The UAE media is playing an important role in raising public awareness about cervical cancer and specific governmental health initiatives such as the HPVV program. Governmental health authorities may want to consider collaborating with the UAE media to develop a communication strategy to reduce the fears and misconceptions surrounding HPVV. Improved parental and adolescent knowledge on the HPVV may lead to increased acceptance and uptake in the UAE society.